Peer-to-peer energy sharing through a two-stage aggregated battery control in a community Microgrid. (15th September 2018) - Long, Chao; Wu, Jianzhong; Zhou, Yue; Jenkins, Nick
Graphical abstract: Highlights: Two-stage control is a feasible solution for P2P energy sharing in low voltage networks. Two-stage control requires limited measurement and one-way communication. P2P energy sharing reduces energy bills of a community by 30%. P2P sharing increases annual self-consumption by 10–30%, and self-sufficiency by ∼20%. With a proper compensation price, P2P sharing ensures every customer be better off. Abstract: Peer-to-peer (P2P) energy sharing allows the surplus energy from distributed energy resources (DERs) to trade between prosumers in a community Microgrid. P2P energy sharing is being becoming more attractive than the conventional peer-to-grid (P2G) trading. However, intensive sensing and communication infrastructures are required either for information flows in a local market or for building a central control system. Moreover, the existing pricing mechanisms for P2P energy sharing could not ensure all the P2P participants gain economic benefits. This work proposed a two-stage aggregated control to realize P2P energy sharing in community Microgrids, where only the measurement at the point of common coupling (PCC) and one-way communication are required. This method allows individual prosumers to control their DERs via a third party entity, so called energy sharing coordinator (ESC). In the first stage, a constrained non-linear programming (CNLP) optimization with a rolling horizon was used to minimize the energy costs of the community. In the second stage, a rule based control was carried out updating the control set-points according to the real-time measurement. The benefits of P2P energy sharing were assessed from the community's as well as individual customers' perspective. The proposed method was applied to residential community Microgrids with photovoltaic (PV) battery systems. It was revealed that P2P energy sharing is able to reduce the energy cost of the community by 30% compared to the conventional P2G energy trading. The modified supply demand ratio based pricing mechanism ensures every individual customer be better off, and can be used as a benchmark for any P2P energy sharing model. For consumers, the electricity bill is reduced by ∼12.4%, and for prosumers, the annual income is increased by ∼£57 per premises.